Gaya kepimpinan pengetua wanita dan hubungannya dengan tahap motivasi guru sekolah menengah - Ramli, Norhannan; Abdul Hamid, Jamaliah (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2006)
The main objective of this research is to observe the teachers’ perception towards the leadership style of woman principals and also its relationship with the level of teachers’ motivation in secondary schools in Kajang, Selangor. This descriptive quantitative research is done through a survey using The Leader Behavior Description Questionnaire (LBDQ) and A Questionnaire Measure of Individual Differences in Achieving Tendency (QMAT). This research involve 203 respondents from seven secondary schools in Kajang, Selangor. The research data is analyzed based on frequency, percentage, mean, standard deviation, ANOVA and Pearson correlation analysis, with the level of ± = .05. The result obtained shows that the teachers’ perception towards the leadership style of woman principals in secondary schools in Kajang is at moderate satisfactory level. Even though the task-based structure is more dominant as compared to the consideration dimension in the leadership style of women principals, both dimensions are at moderate satisfactory level. In the aspect of motivation, it is found that the result shows that the level of the teachers’ motivation towards their work is at moderate satisfactory level. The study also found that the teachers’ demography factors did not bring significant difference in the teachers’ perception towards the leadership style of woman principals. Besides that, the result showed that only age factor gave significant difference in the level of teachers’ motivation as compared to other demography factors. However, there is a significant relationship between the level of the teachers’ motivation and the teachers’ perception towards the leadership style of woman principals. The higher the level of the teachers’ perception towards the leadership style of woman principals, the higher the level of the teachers’ motivation. This study supports the findings of other studies that the leadership style among the woman principals affect the level of teachers’ motivation in schools.